Polycondensation of kraft-lignin toward value-added biomaterials: carbon aerogels. Issue 1 (1st January 2021) - Aufischer, Gottfried; Kamm, Birgit; Paulik, Christian
ABSTRACT: Carbon aerogels are versatile materials for value-added applications such as supercapacitors, insulation materials, and super absorbers. In this work, a way to produce carbon aerogels from kraft lignin which is an abundant waste product from the pulp and paper industry is presented. This was achieved by forming hydrogels of lignin and formaldehyde which were then subjected to solvent exchange and extraction with supercritical CO2 . The resulting aerogels were converted into carbon aerogels by means of pyrolysis. The characterization was performed by gas adsorption and scanning electron microscopy that showed highly porous carbon aerogels with a specific surface area up to almost 600 m 2 g −1 which is relevant for technical applications.